Fat Grafting With Lymphedema Fat: From Trash to Treasure? - Hartiala, Pauliina; Steiner, Aida K.; Niemi, Tarja (Ovid Technologies (Wolters Kluwer Health), 2025)
Liposuction is a common procedure for patients with lymphedema with nonpitting adipose tissue hypertrophy. However, routinely, the lipoaspirate is discarded. Experimental studies have shown that adipose-derived stem cells in fat may enhance the regenerative and lymphangiogenic effects of the fat. Recent evidence has shown that lymphedema fat is enriched in adipose-derived stem cell populations, thus making it an interesting regenerative option. This article introduces a novel surgical technique using the lipoaspirate of a patient with lymphedema for regenerative purposes. A 42-year-old woman developed lymphedema 18 months after mastectomy and axillary lymph node dissection surgery. The patient underwent upper limb liposuction and latissimus dorsi flap reconstruction of the breast. Lipofilling of the flap and axillary area after scar release was performed using suctioned lymphedema fat. The results showed a sustained reduction in the volume of the lymphedema arm, an improved lymphatic transport index, decreased fluid extravasation, and new lymphatics in the upper arm. At 64-month follow-up, the patient had good breast symmetry, had minimal swelling of the lymphedema arm, and rarely used compression garments. This report is the first to use lymphedema fat for regenerative purposes, differentiating it from existing literature that uses healthy fat. In conclusion, successful dual-effect fat grafting with lymphedema fat presents a promising avenue for further investigation. This innovative approach addresses breast cancer-related lymphedema and offers potential benefits in regenerative and lymphangiogenic effects without the need for microsurgical expertise. This case report emphasizes the importance of exploring this novel option for future research and clinical applications.